2013
DOI: 10.1016/j.jascer.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Resorbable calcium sulfates with tunable degradation rate

Abstract: The calcium sulfate (CS) tablets exhibit excellent osteoinductive and osteoconductive characteristics, they can be used to repair bone defects. However, the degradation rate of CS tablets is very fast. The present study demonstrates, for the first time, that the degradation rate of CS tablets can be manipulated through the use of sintering technique. Firing the CS tablets to a temperature of 1100 • C increases their relative density to a value above 90%. The density can be further enhanced to above 95% through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…It was found that the scaffolds without nHAp were nearly completely degraded within 21 days. Fast degradability of CaSO4 was also confirmed by Kuo et al [30]. After adding the nHAp, the degradation was obviously delayed and slowed gradually with increasing nHAp.…”
Section: Degradability and Phsupporting
confidence: 58%
“…It was found that the scaffolds without nHAp were nearly completely degraded within 21 days. Fast degradability of CaSO4 was also confirmed by Kuo et al [30]. After adding the nHAp, the degradation was obviously delayed and slowed gradually with increasing nHAp.…”
Section: Degradability and Phsupporting
confidence: 58%
“…Various approaches have been proposed to decrease the degradation rate of CS pellets [6][7][8]12]. However, previous studies demonstrated that reduction of degradation rate without sacrificing compressive strength is challenging [5].…”
Section: Discussionmentioning
confidence: 99%
“…The result was a higher compressive strength for the sintered CS pellets. More importantly, the degradation rate was reduced [12]. The sintered CS pellets with sintering additives exhibited low cytotoxicity [12].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations